2012
DOI: 10.1209/0295-5075/97/17009
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of domain walls using a spin-polarized STM

Abstract: The manipulation of a ferromagnetic domain wall using a Spin-Polarized Scanning Tunneling Microscope (SP-STM) has been studied by means of a Landau-Lifshitz-Gilbert spin dynamics. We demonstrate that a ferromagnetic transverse domain wall can be shifted by the injection of a spin-polarized tunnel current. Depending on the tip polarization different scenarios occur where the domain wall will be pushed or pulled. Further, we show the possibility to reverse the magnetization inside the domain wall by using the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In an independent study, Yamada et al repeated the same measurement on a system with Mn on top of Fe(001), but found the domain-wall width to be nearly independent of the Mn thickness [19]. Similar frustrated spin configurations have also been reported in other systems [8,9,[20][21][22][23][24][25][26][27][28][29][30]. The frustration induced domain wall in nanorings is considered to lead to potential logic and memory applications [31].…”
Section: Introductionmentioning
confidence: 72%
“…In an independent study, Yamada et al repeated the same measurement on a system with Mn on top of Fe(001), but found the domain-wall width to be nearly independent of the Mn thickness [19]. Similar frustrated spin configurations have also been reported in other systems [8,9,[20][21][22][23][24][25][26][27][28][29][30]. The frustration induced domain wall in nanorings is considered to lead to potential logic and memory applications [31].…”
Section: Introductionmentioning
confidence: 72%
“…The actual limit in case of a spin S=1/2 system is 40 spins using exact diagonalization. In comparison to the 40 spins, we have approximately 4 million spins in case of the classical description [35][36][37][38][39]. The reason for the restriction to a small number of quantum spins are the large matrices we have to deal with.…”
Section: Comment On the Practical Usementioning
confidence: 99%
“…2b) Despite the creation and annihilation of Skyrmions the scanning tunneling microscope can be also used to move Skyrmions. The possibility to shift domain walls has been discussed in [22,23]. Fig.…”
Section: The First Step Toward This Direction Has Been Already Done mentioning
confidence: 99%